Pengaruh Diversitas Kebangsaan Board of Director dan Kepemilikan Blockholders terhadap Nilai Perusahaan: Studi pada Perusahaan Publik di Indonesia - Kesaulya, Feby Astrid; Febriany, Novita (Kompartemen : Jurnal Ilmiah Akuntansi, 2019)
The purpose of this study is to prove that there is influence of the implementation of good corporate governance to the value of the company. The implementation of corporate governance in this study is represented by the nationality diversity of board of directors and ownership of blockholders. The nationality diversity of the board of directors in this study is represented by foreign board of directors, foreign board of commissioners, and foreign CEO / CFO. This study was conducted on Indonesian public corporations using 363 firm years sample. The results of this study show different results from previous studies. This study shows that the implementation of good corporate governance in the form of nationality diversity board of directors measured using foreign board of directors, foreign board of commissioners and foreign CFO / CEO does not affect the value of the company. In addition, ownership of blockholders also has no effect on the value of the company.